(untitled) (Historia, 2021)
On 28 March 1979 Prof. F.A. van Jaarsveld was prevented from presenting a lecture at a public lecture by a group of activists. They made interjections and then tarred and feathered him. In the study an attempt is made to describe the incident in the context of the 1960s and 1970s and analyse the historical consciousnesses of the different parties within the context of Nietzsche's classification of antiquarianism, monumentalism and criticism.